Spatiotemporal footprints and health risk assessments of odor emissions from large-scale food waste anaerobic digestion plants - Lin Cui; Ziyang Lou; Long Kong; Farooq Muhammad Amjad; Zhijie Wang; Changfu Yang; Jun Si; Meilan Zhang; Luochun Wang; Zhaowen Cheng (Atmospheric Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Room-Temperature Fabrication of Dual-Functional SiO2/TiO2 Coating for Photovoltaic Efficiency Enhancement: From Laboratory Development to Field Validation - Pengge Wang; Xinwei Li; Ning Zhang; Yue Zhai; Zhenyu Wang; Long Cui; Suixin Liu; Wingkei Ho; Yu Huang; Shun-cheng Lee (Aerosol Science and Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Molecular mechanisms underlying microplastics-induced inhibition of lateral root development in tomato (Solanum lycopersicum L.) - Rongchao Yang; Mengjiao Chen; Long Cheng; Yilan Cui; Chengyong Li; Yueqin Zhang (Journal of Environmental Management, 2025)

Experimental investigation on local scour evolution around a circular monopile in the silty bed under wave-current combinations - Chunguang Yuan; Mingxiao Xie; Jinquan Wang; Xiaoliang Xia; Long Xiao; Na Zhang; Cheng Cui (Coastal Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electric vehicle range prediction considering real-time driving factors and battery capacity index - Xinwei Ma; Jiaao Li; Hongjun Cui; Long Cheng; Yanjie Ji; Jianbiao Wang (Transportation Research Part D: Transport and Environment, 2025)

What influences intermodal Choices: Metro-Centric, Bus-Centric, Hybrid? insights from Machine learning Approaches - Xinwei Ma; Xiaolin Tian; Hongjun Cui; Mingjia He; Jianbiao Wang; Long Cheng (Transportation Research Part D: Transport and Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Current status of molecular rice breeding for durable and broad-spectrum resistance to major diseases and insect pests - Xiaoyan Cheng; Guohua Zhou; Wei Chen; Lin Tan; Qishi Long; Fusheng Cui; Lei Tan; Guoxing Zou; Yong Tan (Theoretical and Applied Genetics, 2024)
In the past century, there have been great achievements in identifying resistance ( R ) genes and quantitative trait loci (QTLs) as well as revealing the corresponding molecular mechanisms for resistance in rice to major diseases and insect pests. The introgression of R genes to develop resistant rice cultivars has become the most effective and eco-friendly method to control pathogens/insects at present. However, little attention has been paid to durable and broad-spectrum resistance, which determines the real applicability of R genes. Here, we summarize all the R genes and QTLs conferring durable and broad-spectrum resistance in rice to fungal blast, bacterial leaf blight (BLB), and the brown planthopper (BPH) in molecular breeding. We discuss the molecular mechanisms and feasible methods of improving durable and broad-spectrum resistance to blast, BLB, and BPH. We will particularly focus on pyramiding multiple R genes or QTLs as the most useful method to improve durability and broaden the disease/insect spectrum in practical breeding regardless of its uncertainty. We believe that this review provides useful information for scientists and breeders in rice breeding for multiple stress resistance in the future.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Evaluation and determinants of metro users' regularity: Insights from transit one-card data - Xinwei Ma; Xiaolin Tian; Zejin Jin; Hongjun Cui; Yanjie Ji; Long Cheng (Journal of Transport Geography, 2024)

An improved multi-filter fusion indoor localization algorithm based on INS and UWB - Long Cheng; Chen Cui; Zhijian Zhao; Yuanyuan Shi (Earth Science Informatics, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Flavonoid components and gene expression analysis reveal flower pigmentation difference between Magnolia biondii and its variety M. biondii var. purpurascens - Ning-hang Wang; Meng-yi Dai; Gang Zheng; Peng-jie Chang; Ling-juan Xuan; Zhi-gao Liu; Ya-ling Wang; Shao-yu Cheng; Zhuo-wei Wang; Hai-long Wang; Cui-hua Gu; Chao Zhang; et al. (Trees, 2022)

Dammarane-type saponins from Gynostemma pentaphyllum and their cytotoxicities - Wei-Ye Cui; Yulian Jin; Hui Liu; Ma-Li Zu; Xin-Fang Zhai; Ce Yang; Yu-Long Gu; Yong Cheng; Xiang-Lan Piao (Natural Product Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Erosion and transport mechanisms of mine waste along gullies - Xing-hua Zhu; Yi-fei Cui; Jian-bing Peng; Cheng Jiang; Wei-long Guo (Journal of Mountain Science, 2019)

Apparent permeability and representative size of shale: a numerical study on the effects of organic matter - Jiangfeng Cui; Long Cheng; Lei Li (Computational Geosciences, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A preliminary study on ore-forming environments of Xianglushan-type iron deposit and the weathering mineralization of Emeishan basalt in Guizhou Province, China - Guofan Cheng; Youping Liu; Hansheng Long; Tao Cui; Ning Yu (Acta Geochimica, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)